Optimizing the @official.usu Instagram Account to Improve the Institution's Image - Afifah, Tsani; Masril, Munzaimah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2024)
This article is entitled